A study on EEG-based brain electrical source of mild depressed subjects. Issue 3 (July 2015) - Li, Xiaowei; Hu, Bin; Xu, Tingting; Shen, Ji; Ratcliffe, Martyn
Highlights An experiment measure eye movement and EEG simultaneously. Apply EEG source location to detect abnormal regions of mild depression. Different data to analyses difference between mild depressed subjects and health people.